2021
DOI: 10.1093/tropej/fmab013
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Response to Pediatric Scrub Typhus in South India: Is Clinical Failure to Azithromycin to be Worried?

Abstract: Background Scrub typhus is typically associated with a rapid defervescence and clinical improvement within 48 h of initiation of appropriate antibiotics. But increasing reports of resistance to anti-rickettsial medications in scrub typhus are being reported in the literature. Methods This is a retrospective observational study of children up to the age of 14 years admitted between July 2017 and March 2020, to a private medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There were five RCTs [ 18 , 21 , 25 – 27 ]. Four studies included only paediatric patients (less than 14-18 years) [ 21 , 22 , 24 , 25 ]. The remaining six incorporated either adults or individuals of any age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were five RCTs [ 18 , 21 , 25 – 27 ]. Four studies included only paediatric patients (less than 14-18 years) [ 21 , 22 , 24 , 25 ]. The remaining six incorporated either adults or individuals of any age.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies excluded the use of antibiotics (active for scrub typhus) before presentation (Supplementary Table 4 ). Only one study explicitly mentioned that co-infections were ruled out [ 24 ]. Four studies exclusively focussed on patients with mild scrub typhus [ 21 , 25 – 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who did not achieve defervescence after 72 hours of the interventional drug were labeled as treatment failure cases and were switched over to the alternate drug, but the outcome of these cases was not mentioned. While observational studies have provided conflicting findings, 22,23 a comprehensive meta-analysis of RCTs demonstrated that AZ and DX exhibited similar efficacy in achieving disease cure, although this included mainly adult data. 21 Our study protocol had left the management of children who were labeled as treatment failure to the discretion of the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have given mixed results comparing azithromycin to doxycycline in treating scrub typhus. [17][18][19] Meta-analysis from eligible studies, however, showed that azithromycin was as efficacious as doxycycline in achieving clinical cure and defervescence at 48 h, with the azithromycin group having significantly fewer adverse events and treatment failure. 11,[20][21][22][23][24] Studies have also highlighted an emerging resistance to doxycycline in south and east Asian regions, but both resistant strains were found to be highly sensitive to azithromycin.…”
Section: Discussionmentioning
confidence: 99%